Indian Journal of Nematology 10(2): 1980 (Indian Journal of Nematology, 2024)
EDITORIAL BOARD (1979-81)Chief Editor     - GoPAL SWARUP, Nematology Divn., I. A. R. I., New DelhiEditor                - D. R. DAs GUPTA, Nematology Divn., I. A. R. I., New DelhiMembers          - C. L. SETHI, Nematology Divn., I. A. R. I., New Delhi                           - K. C. SANWAL, N. B. P. G. R., New Delhi                           - ABRAR M. KHAN, Botany Dept., A. M. U., Aligarh                           - S. KHZRA, Zoology Dept., Meerut University, Meerut                           - T. S. MUTHUKKISHNAN, Biology Dept., T. N. A. U., Coimbatore                           - M. S.JAIRAPURI, Zoology Dept., A. M. D., Aligarh